2012
DOI: 10.1017/s0007485312000442
|View full text |Cite
|
Sign up to set email alerts
|

Precocious sexual signalling and mating in Anastrepha fraterculus (Diptera: Tephritidae) sterile males achieved through juvenile hormone treatment and protein supplements

Abstract: Sexual maturation of Anastrepha fraterculus is a long process. Methoprene (a mimic of juvenile hormone) considerably reduces the time for sexual maturation in males. However, in other Anastrepha species, this effect depends on protein intake at the adult stage. Here, we evaluated the mating competitiveness of sterile laboratory males and females that were treated with methoprene (either the pupal or adult stage) and were kept under different regimes of adult food, which varied in the protein source and the sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…While Gomez‐Simuta, Diaz‐Fleischer, Arredondo, Díaz‐Santiz, and Pérez‐Staples () found that female Mexican fruit flies mated by young methoprene‐treated males exhibited normal levels of sexual inhibition, Abraham et al. () found that females of South American fruit fly that mated with 6‐day‐old methoprene‐treated males, the age at which elevated mating propensity and competitiveness is expressed (Liendo et al., ; Segura et al., , ) remated more often and sooner than females mated with mature males that had not received methoprene treatment. These results suggest a decoupling of sexual maturation in terms of mating behaviour and reproductive development in terms of underlying morphology and physiology.…”
Section: Discussionmentioning
confidence: 99%
“…While Gomez‐Simuta, Diaz‐Fleischer, Arredondo, Díaz‐Santiz, and Pérez‐Staples () found that female Mexican fruit flies mated by young methoprene‐treated males exhibited normal levels of sexual inhibition, Abraham et al. () found that females of South American fruit fly that mated with 6‐day‐old methoprene‐treated males, the age at which elevated mating propensity and competitiveness is expressed (Liendo et al., ; Segura et al., , ) remated more often and sooner than females mated with mature males that had not received methoprene treatment. These results suggest a decoupling of sexual maturation in terms of mating behaviour and reproductive development in terms of underlying morphology and physiology.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol has the advantage that it can provide information on both relatively long and close distance recognition. Several examples of the use of walk-in field cages to assess tephritid attraction to different odor sources can be found in the literature (Webb et al 1983, Shelly 2000a, 2000b, López-Guillén et al 2011, Liendo et al 2013, Milet-Pinheiro et al 2014). However, the usefulness of walk-in field cages to assess preference of female flies for pheromones of con-specific vs hetero-specific males has not been evaluated yet.…”
Section: The Role Of Pheromones In Species Recognitionmentioning
confidence: 99%
“…To determine whether Anastrepha fraterculus male pheromones from two different populations were equally attractive to con-specific and hetero-specific females, the methodology of Liendo et al (2013) was adapted, which in turn is an adaptation of the methodology proposed by Shelly (2000a) for Ceratitis capitata (Box 2). The experiments were carried out in a greenhouse of the (IPCL)FAO/IAEA Insect Pest Control Laboratory in Seibersdorf, Austria and involved one population from Piracicaba, São Paulo, Brazil and one from Tucumán, Argentina.…”
Section: The Role Of Pheromones In Species Recognitionmentioning
confidence: 99%
“…This argues against the idea that the lack of benefits associated to methoprene lays on the fact that methoprene is a synthetic compound. Methoprene is similar to JH in chemical structure and, more importantly, its role on A. fraterculus seems to replicate that of JH [55,71,72]. Therefore, the strong preference of females for methoprene-treated males could, still, be associated to other benefits, yet unidentified.…”
Section: Discussionmentioning
confidence: 99%